2023
DOI: 10.1097/ju.0000000000003012
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Short-term Outcomes of Active Surveillance in Men With National Comprehensive Cancer Network Favorable Intermediate-risk Prostate Cancer: The Initial Michigan Urological Surgery Improvement Collaborative Experience

Abstract: Study Need and Importance:There is a lack of realworld evidence on the use of active surveillance (AS) for favorable intermediate-risk prostate cancer (FIRPC) from diverse clinical practice settings. Further, little is known about the short-term oncologic outcomes for men with FIRPC who receive up-front treatment vs those who delay radical prostatectomy (RP). We retrospectively reviewed the Michigan Urological Surgery Improvement Collaborative data to assess the use of AS for men diagnosed with FIRPC and inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In the period of time during which Navigate has been developed, AS is increasingly being used for favourable intermediate-risk PC. 31 While Navigate was initially designed with and for men with LRPC, it is equally relevant for men with intermediate risk PC, and this cohort of men is included in the current RCT. Report the source of funding to develop the patient decision aid and whether funders, authors or their affiliations, stand to gain or lose by choices patients make after using the patient decision aid…”
Section: Discussionmentioning
confidence: 99%
“…In the period of time during which Navigate has been developed, AS is increasingly being used for favourable intermediate-risk PC. 31 While Navigate was initially designed with and for men with LRPC, it is equally relevant for men with intermediate risk PC, and this cohort of men is included in the current RCT. Report the source of funding to develop the patient decision aid and whether funders, authors or their affiliations, stand to gain or lose by choices patients make after using the patient decision aid…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the finding of this survey suggest that AS may be conducted for favorable intermediate-risk prostate cancer in a certain percentage of patients in Japan as it is in the United States. 2,5 The results of this survey highlight several problems regarding the extent of AS usage in Japan. Some respondents indicate that the upper age limit for AS is 90 years or older.…”
Section: Editorial Commentsmentioning
confidence: 91%
“…Furthermore, they reported that about 40% of urologists considered AS for favorable intermediate‐risk patients. Interestingly, the finding of this survey suggest that AS may be conducted for favorable intermediate‐risk prostate cancer in a certain percentage of patients in Japan as it is in the United States 2,5 …”
mentioning
confidence: 89%
See 2 more Smart Citations